Recombinant human zona pellucida protein C produced in Chinese hamster ovary cells binds to human spermatozoa and inhibits sperm-zona pellucida interaction - Marin Briggiler, Clara Isabel (2008)
Recombinant human zona pellucida protein C expressed in Chinese hamster ovary cells associates to the acrosomal region of human spermatozoa and inhibits sperm-zona pellucida interaction in the hemizona assay. Recombinant human zona pellucida protein C may be a useful tool toward the development of diagnostic methods for male factor infertility and the elucidation of the molecular basis of fertilization.